Creative Hub as a Creative Space for Young People of Palu City With Plowright Pattern-Based Design Method - Andi Faidilah; Fuad Zubaidi; Lilies Handayani (Tadulako Science and Technology Journal, 2023)
This res earch is motivated by the increas e in the creative indus try s ector in Palu City, es pecially in the craft, film and performing arts s ubs ectors and als o the adjus tment of s pace for the public in the new normal era so that the urgency of the need for s paces that can facilitate creative activities , es pecially during this pandemic, needs to be provided, es pecially in the Palu City area s o that the title rais ed in the form of "Creative Hub as a Space for Youth Creativity in Palu City" can be a forum for utilizing exis ting potential. The des ign of the Creative Hub of Palu City is intended to provide good interaction for the s urrounding environment and can als o be a des ign s olution in the new normal era and in accordance with the context of the city of Palu for the completion of the des ign of the Creative Hub of Palu City us ing the de s ign method of Plowright Pattern bas ed des ign where the key operation of patterns / s hapes in architecture as s tructuring, organization and pattern compos ition games . The des ign of the Creative Hub of Palu City is expected to be a place that can s upport th e creativity and productivity of creative indus try players and als o the general public and can be a planning s olution for the Covid -19 pandemic-friendly des ign principles .